2016
DOI: 10.1111/jvs.12411
|View full text |Cite
|
Sign up to set email alerts
|

How plot shape and spatial arrangement affect plant species richness counts: implications for sampling design and rarefaction analyses

Abstract: Questions How does the spatial configuration of sampling units influence recorded plant species richness values at small spatial scales? What are the consequences of these findings for sampling methodology and rarefaction analyses? Location Six semi‐natural grasslands in Western Eurasia (France, Germany, Bulgaria, Hungary, Italy, Turkey). Methods In each site we established six blocks of 40 cm × 280 cm, subdivided into 5 cm × 5 cm micro‐quadrats, on which we recorded vascular plant species presence with the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…Most likely, rectangular plots captured more spatial heterogeneity. A similar effect can be observed for species richness counts, where more species can be found in elongated plots (Güler et al 2016). Both regular and random arrangements of sampling plots were able to capture landscape properties similarly well.…”
Section: Use Casesupporting
confidence: 70%
“…Most likely, rectangular plots captured more spatial heterogeneity. A similar effect can be observed for species richness counts, where more species can be found in elongated plots (Güler et al 2016). Both regular and random arrangements of sampling plots were able to capture landscape properties similarly well.…”
Section: Use Casesupporting
confidence: 70%
“…The 2006 field work data were sampled with circular plots, whereas in the 2017 inventory, square plots were used. In previous studies, it has been found that plot shape has an effect on how many species are observed within the plot (Bacaro et al., ; Güler et al., ). Thus, the differently shaped plots might have had an effect on the observed species and PFTs, their percentage coverages and modeled clusters, but as indicator species and PFTs were closely similar for both data sets (see ), we do not see that the differing plot shapes had any major impact on our results.…”
Section: Discussionmentioning
confidence: 98%
“…We calculated the cumulative richness of 24 discontinuous 1‐m 2 quadrats within a 1000‐m 2 area, and used it as proxy for site‐level richness (Güler et al. ). Analyses were conducted separately for the two grassland types, DBERG and MBELT.…”
Section: Methodsmentioning
confidence: 99%